Experimental data of phospholipid supplementary in full fishmeal replacement diets on growth indices, whole body nutrient composition, muscle fatty acid composition, haematocrit value and serum lysozyme activity in Malaysian mahseer (Tor tambroides) - Sohel Mian; Sairatul Dahlianis Ishak; Noordiyana Mat Noordin; Md Abdul Kader; Yazed Muhammad Abduh; Helena Khatoon; Ambok Bolong Abol-Munafi (Data in Brief, 2020)
The data collection was initiated to evaluate the effects of supplementary phospholipid to non-fishmeal based diet in order to make functional diets for the Malaysian Mahseer, Tor tambroides. Four iso-nitrogenous and iso-lipidic diets were formulated to consist 100% fishmeal (FM100), 0% fishmeal or full fishmeal replacement (FM0), and 0% fishmeal supplemented with 4% phospholipids (FM0+4%PL), 6% phospholipids (FM0+6%PL). A 60-day feeding trial was conducted and data collection was carried out for the following parameters; growth indices, somatic parameters, whole body nutrient composition, muscle fatty acid composition, haematocrit value and serum lysozyme activity. Fish fed FM0 diets showed significantly poor performance (P < 0.05) for all parameters. Fish showed improved growth, better whole body protein content and higher lysozyme activity when fed FM100 and phospholipid supplemented diets. In general, the current study validated that dietary PL supplementation may possibly improve the growth and survival of juvenile T. tambroides fed non-fishmeal based diets. Findings of this research could contribute in the aquaculture development of T. tambroides. Keywords: Fish nutrition, Feed formulation, Nutrient supplement, Dietary phospholipid, Fatty acid, Growth performance, Haematology